Fracture of Nano and Engineering Materials and Structures
DOI: 10.1007/1-4020-4972-2_226
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Laboratory Specimen on Fatigue Crack Growth Rate

Abstract: Over the past thirty years, laboratory experiments have been devised to develop fatigue crack growth rate data that is representative of the material response. The crack growth rate data generated in the laboratory is then used to predict the safe operating envelope of a structure. The ability to interrelate laboratory data and structural response is called similitude. In essence, a nondimensional term, called the stress intensity factor, was developed that includes the applied stresses, crack size and geometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…There is also an even smaller difference between the FCG rates measured in thin and thick specimens. A similar behavior was reported by Forth et al in FCG tests performed under constant load conditions, when they tested C(T), M(T), and ESE(T) specimens, using the same material as well as specimen width (w) and thickness (t) [23,24]. They concluded that the differences observed in FCG rates were probably caused by environmental effects and roughness of the crack faces, which could explain the variation reported in these results.…”
Section: Resultssupporting
confidence: 85%
“…There is also an even smaller difference between the FCG rates measured in thin and thick specimens. A similar behavior was reported by Forth et al in FCG tests performed under constant load conditions, when they tested C(T), M(T), and ESE(T) specimens, using the same material as well as specimen width (w) and thickness (t) [23,24]. They concluded that the differences observed in FCG rates were probably caused by environmental effects and roughness of the crack faces, which could explain the variation reported in these results.…”
Section: Resultssupporting
confidence: 85%
“…As a support of the theories against the similitude hypothesis, we mention the experimental results by Newman et al (2004), who observed that "in the threshold regime there is something missing in the (closure) model", and those by Forth et al (2006), revealing that similitude does not hold in Region I (the near-threshold region) and also in the lower portion of Region II. To solve this problem, Molent et al (2006) and Jones et al (2007) have recently proposed a generalized Frost and Dugdale (1958) crack growth law, assuming that the crack growth rate is proportional to the accumulated plastic strain, averaged over a characteristic length ahead of the crack tip:…”
Section: Comparison With the Generalized Frostmentioning
confidence: 81%
“…Unlike monotonic properties, determination of cyclic attributes requires more rigorous tests, sophisticated measurements of local flow behaviour, crack lengths, etc. Moreover, the standardized experiments are very lengthy, expensive and by themselves do not absolutely address the inherent material response to the damage accurately . The persistent hurdle in establishing a uniform law is that the fatigue is a very strongly microstructure‐sensitive phenomenon.…”
Section: Motivation and Objectivementioning
confidence: 99%